Gender Quotas, Competitions, and Peer Review: Experimental Evidence on the Backlash Against Women - Andreas Leibbrandt; Liang Choon Wang; Cordelia Foo (Center for Economic Studies and ifo Institute (CESifo), 2015)
This study experimentally investigates gender quotas in light of peer review. We investigate competitions with and without gender quotas and a peer review process that allows for sabotage. Our findings show that the possibility of peer sabotage renders the gender quota ineffective in encouraging women to enter tournaments and reversing gender pay gaps. Moreover, we provide evidence of a severe backlash against women, as they become targets of sabotage under gender quotas. Interestingly, this is the result of women focusing on sabotaging each other while men sabotage indiscriminately. Our results have implications for the use of quotas to mitigate the under-representation and underperformance of minority groups in environments in which peer sabotage is possible.
Keywords: C93; J23; J33; 330; affirmative action; gender quota; gender gap; labor market; sabotage; competition; tournament